1999
DOI: 10.1021/ja9919635
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses, Structures, Physical Properties, and Theoretical Study of LaCu0.40Te2, NdCu0.37Te2, SmCu0.34Te2, GdCu0.33Te2, and DyCu0.32Te2

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 100 leading journals. To access a ChemInform Abstract of an article which was published elsewhere, please select a “Full Text” option. The original article is trackable via the “References” option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
52
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 53 publications
3
52
0
Order By: Relevance
“…The formal oxidation states of Te atoms are closely correlated with Te}Te bonding distances. The relationship between the charge on Te and bond distances has been discussed elsewhere (25).…”
Section: Resultsmentioning
confidence: 99%
“…The formal oxidation states of Te atoms are closely correlated with Te}Te bonding distances. The relationship between the charge on Te and bond distances has been discussed elsewhere (25).…”
Section: Resultsmentioning
confidence: 99%
“…LaCuxTe2 (0.28 ≤ x ≤ 0.50) and Gd3Cu2Te7 are both tellurides whose crystal structures comprise linear undistorted tellurium chains (Figure 4) [87][88][89]98]. The occurrence of such undistorted linear tellurium chains is noteworthy, because low-dimensional tellurium building units, largely in the forms of tellurium square nets, often undergo structural distortions due to the formations of charge density waves [116][117][118][119][120][121].…”
Section: Tendencies Within Bonding Motifs In Compounds With Polyanionmentioning
confidence: 99%
“…Corresponding to the formations of charge density waves, the structural distortions in low-dimensional structural fragments are associated with the openings of band gaps at the Fermi levels, which reduce the electronic energies relative to those of the metallic states and, hence, alleviate electronic instabilities below certain transition temperatures [122,123]. Notably, the measurements of the temperature-dependent electrical conductivity behavior for LaCuxTe2 (0.28 ≤ x ≤ 0.50) revealed that this telluride should be a semiconductor [88,89]. Additional inspections of the X-ray diffraction patterns of SmCu0.34Te2 being isostructural with LaCuxTe2 (0.28 ≤ x ≤ 0.50) bared the presence of weak reflections pointing to a superstructure along the direction of the linear tellurium chains.…”
Section: Tendencies Within Bonding Motifs In Compounds With Polyanionmentioning
confidence: 99%
“…The formation of the compounds RCu x Te 2 (R = Ce, Pr, Nd, Sm, Gd and Dy) isostructural to LaCu 0.28 Te 2 have been established in Refs. [4][5][6].…”
Section: Introductionmentioning
confidence: 99%